Human Genome Editing and Sickle Cell Disease in Canada: Urgent and Unresolved Ethical Considerations - Klimenko, Maria; Tonkens, Ryan (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2025)
Some countries are already approving therapeutic applications of human genome editing. For example, recently the United Kingdom and USA have approved Casgevy as part of a treatment protocol for sickle cell disease. Should Canada follow this lead? Here we discuss the most important, yet unresolved, ethical issues in a Canadian context, and argue that much more public engagement and deliberation is needed.